Evaluating fertilizer effects on growth, yield, and nutritional value of Tiger Nut (Cyperus esculentus L.) in Ghana - Novor, Samuel; Santo, Kwadwo Gyasi; Abdul, Khalid Aziz; Owusu-Kwarteng, James; Atakora, Kwabena; Eyahanyo, Felix (Australian journal of crop science, 2025)
This study assessed the effects of organic and inorganic fertilizers, both individually and in combination, on the mineral composition, yield, and soil chemical properties of Cyperus esculentus (tiger nut) tubers. The experiment was carried out over three growing seasons in the forest-savanna transition zone, where the soil is classified as Acrisol. A 2 x 4 factorial arrangement within a Randomized Complete Block Design (RCBD) was employed, comparing two varieties of tiger nut (brown and black) under four fertilization treatments: no fertilizer (control), 2,000 kg ha⁻¹ poultry manure, 300 kg ha⁻¹ NPK 15:15:15, and a combination of 1,000 kg ha⁻¹ poultry manure + 150 kg ha⁻¹ NPK 15:15:15. The findings indicated that the two tiger nut varieties responded similarly across all measured parameters. The application of poultry manure, both alone and in combination with NPK 15:15:15, significantly improved soil properties, particularly calcium, sodium, hydrogen, and aluminum levels, across all seasons. Additionally, the combined treatment of poultry manure and NPK 15:15:15 consistently enriched the tubers with essential nutrients such as phosphorus, potassium, iron, manganese, copper, and zinc throughout the study period. The sole use of poultry manure enhanced the levels of phosphorus and potassium in the nuts across all seasons. In conclusion, the combined application of poultry manure and NPK 15:15:15 significantly increased tiger nut yield, improved soil nutrient content, and enhanced the nutritional quality of the nuts compared to the control and other treatments. Therefore, this combined fertilization approach is recommended for farmers as it effectively boosts both the yield and quality of tiger nuts, providing a sustainable option for soil fertility management.